Determinasi Pertumbuhan Ekonomi Daerah di Provinsi Jambi - Kurniati Setyaningrum; Siti Hodijah; Nurhayani Nurhayani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study examines the dynamic progression of Regional Original Revenue (PAD), the realization of Domestic Investment (PMDN), the size of the labor force, infrastructure availability, and their implications for economic growth across 11 regencies and municipalities in Jambi Province over the period 2017–2023. The analysis employs a panel data regression model, utilizing a combination of time-series and cross-sectional data sourced from Statistics Indonesia and the Regional Investment and One-Stop Integrated Services Office. The empirical findings reveal that PAD experienced a growth rate of 5.39 percent. In contrast, PMDN and the labor force displayed fluctuating patterns, with percentage changes of 905.97 percent and 1.68 percent, respectively. Infrastructure development and economic growth recorded increases of 0.51 percent and 4.04 percent. Further analysis demonstrates that PAD, labor force participation, and infrastructure exert a positive and statistically significant influence on economic growth. Conversely, PMDN does not exhibit a statistically significant effect on regional economic growth within the observed period.